Household survey results Slave lake, AB 2012 : technical report - Kulig, Judith Celene; Townshend, Ivan; Awosoga, Olu A.; Shepard, Blythe; Reimer, William; Edge, Dana; Lightfoot, Nancy (University of Lethbridge, 2012)
Results of a household survey that was conducted to assess the following variables within a larger population within the Slave Lake area postwildfire: 1. What were the evacuation experiences of the Slave Lake area residents? 2. What were the impacts of the wildfires on the families and children that experienced it? 3. What were the impacts of the wildfires on the community’s social relations?